P-V Criticality of Conformal Anomaly Corrected AdS Black Holes - Jie-Xiong Mo; Wen-Biao Liu (Advances in High Energy Physics)
The effects of conformal anomaly on the thermodynamics of black holes are investigated in this paper from the perspective of P-V criticality of AdS black holes. Treating the cosmological constant as thermodynamic pressure, we extend the recent research to the extended phase space. Firstly, we study the P-V criticality of the uncharged AdS black holes with conformal anomaly and find that conformal anomaly does not influence whether there exists Van der Waals like critical behavior. Secondly, we investigate the P-V criticality of the charged cases and find that conformal anomaly influences not only the critical physical quantities but also the ratio Pcrc/Tc. The ratio is no longer a constant as before but a function of conformal anomaly parameter α~. We also show that the conformal parameter should satisfy a certain range to guarantee the existence of critical point that has physical meaning. Our results show the effects of conformal anomaly.